Sustainable prospective of some selected species from Moraceae and Araceae family of Northeast India: A Review - Das, Jinti Moni; Sarma, Barsha; Nath, Namita; Borthakur, Mridul Kr. (Plant Science Today, 2022)
The north-eastern region of India is a rich hub of floristic diversity. The intricate relationship between forest resources and indigenous people is a key to sustainability and rural livelihood. The objective is to review on some plants that has possible function for sustainable source of food. The regional people have been utilizing various species of the two commonly available angiosperm plant families viz. Araceae (Alocasia macrorrhizos, Colocasia esculenta) and Moraceae (Ficus carica, F. semicordata, F. auriculata) as a source of food, herbal medicine, and fodder plants. A variety of natural compounds found among various members of these two families are alkaloids viz., Alocasin B, ?-monopalmitin in A. macrorrhizos; flavonoids viz., orientin, isovitexin, in C. esculenta; betulinic acid, lupeol in F. auriculata; quercetin, leucine, tryptophan in F. carica; terpenoids like ?-thuzene, ?-pinene in F. semicordata; besides the presence of phenols, tannins, saponins, fats, carbohydrates, amino acids and proteins, minerals like Ca, Mg, K, Mn, Cu. The rich tradition of indigenous herbal healthcare practices for curing various ailments are widespread among the rural communities. The review entails the indigenous practices with pharmacological efficacy, phytochemistry and sustainable prospects of Moraceae and Araceae which are widely used in food, nutraceutical and medicinal aspects. These lesser-known plant species may attribute to ecological restoration, bioremediation of toxic compounds, discovery of novel therapeutics, sources of carbon sink in near future as well.